Spatial Localization of Electromagnetic Radiation Sources by Cascade Neural Network Model with Noise Reduction - Ilic, M.; Stankovic, Z.; Males-Ilic, N. (Společnost pro radioelektronické inženýrství, 2023)
In this paper, the Direction of Arrival - DoA estimation for two mobile sources was performed by using the Single Multilayer Perceptron (MLP) neural network model (SMLP-DoA) and the Cascade MLP model(CMLP). The latter model consists of two neural networks connected in a cascade where the outputs of the first MLP that rejects noise represent the inputs to the second network in a cascade. The outputs of the neural network models determine the direction of arrival of the incoming signals. Two cases were considered, in the first case the neural networks were trained on the samples that were without noise, and in the second with samples containing noise. Both considered neural network models were tested with noisy samples. The results of these two neural models are compared to the results achieved by the RootMUSIC algorithm. The presented results show that the proposed CMLP model has a higher accuracy in determining the angular positions of sources compared to the classical SMLP-DoA model and the RootMUSIC algorithm. Moreover, the CMLP model executes significantly faster compared to the model based on the RootMUSIC algorithm.
Keywords: The direction of Arriva (DoA) estimation; artificial neural networks; Multilayer Perceptron (MLP); single MLP; cascade MLP; RootMUSIC algorithm